ASSESSMENT OF ENVIRONMENTAL CAPACITY OF THUY TRIEU - CAM RANH WATERS - Thu, Phan Minh; Huan, Nguyen Huu; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2014)
Based on the collected and investigated data in the period of 2011-2012 and the plan of socio-economic development of the Thuy Trieu - Cam Ranh coastal areas, this paper estimates the water’s environmental carrying capacity to manage them for sustainable development. The results show that, the volume of organic matter (by COD) met the potential carrying capacity of the waters. For dissolved inorganic nutrients, the nitrate and ammonia/ammonium reached to the available carrying capacity of the waters in dry season, whereas phosphate was the potential carrying capacity of the waters in rainy season. Within the socio-economic development plan of the Thuy Trieu - Cam Ranh coastal areas in 2015 and 2020, the carrying capacity of the waters is predicted to be overloaded by organic matter. Therefore, it is necessary to propose technical solutions to reduce the total of waste matters from socio-economic activities as well as to enhance the self-purification capability of the waters to protect and improve their environmental quality.